Clinical and Genetic Factors Associated With Severe Hematological Toxicity in Glioblastoma Patients During Radiation Plus Temozolomide Treatment: A Prospective Study. (October 2015) - Lombardi, Giuseppe; Rumiato, Enrica; Bertorelle, Roberta; Saggioro, Daniela; Farina, Patrizia; Della Puppa, Alessandro; Zustovich, Fable; Berti, Franco; Sacchetto, Valeria; Marcato, Raffaella; Amadori, Alberto; Zagonel, Vittorina
Abstract : Background: Temozolomide (TMZ) administered daily with radiation therapy (RT) for 6 weeks, followed by adjuvant TMZ for 6 cycles, is the standard therapy for newly diagnosed glioblastoma (GBM) patients. Although TMZ is considered to be a safe drug, it has been demonstrated to cause severe myelotoxicity; in particular, some case reports and small series studies have reported severe myelotoxicity developing during TMZ and concomitant RT. We performed a prospective study to analyze the incidence of early severe myelotoxicity and its possible clinical and genetic factors. Patients and Methods: From November 2010 to July 2012, newly diagnosed GBM patients were enrolled. They were eligible for the study if they met the following criteria: pathologically proven GBM, age 18 years and older, an Eastern Cooperative Oncology Group performance status of 0 to 2, adequate renal and hepatic function, and adequate blood cell counts before starting TMZ plus RT. Grading of hematologic toxicity developing during radiation and TMZ was based on the National Cancer Institute Common Terminology Criteria for Adverse Events version 4.0. Clinical factors from all patients were recorded. The methylation status and polymorphic variants of O 6 -methylguanine-DNAmethyl-transferase gene in peripheral blood mononuclear cells, and polymorphic genetic variants of genes involved in the pharmacokinetics and pharmacodynamics of TMZ, were analyzed. For genetic analyses, patients with toxicity were matched (1:2) for age, performance status, anticonvulsants, and proton pump inhibitors with patients without myelotoxicity. Results: We enrolled 87 consecutive GBM patients: 32 women and 55 men; the average age was 60 years. During TMZ and RT, 4 patients (5%) showed grade 3-4 myelotoxicity, and its median duration was 255 days. Predictor factors of severe myelotoxicity were female sex, pretreatment platelet count of ⩽3, 00, 000/mm 3, methylated O 6 -methylguanine-DNA methyltransferase promoter in the hematopoietic cell system, and specific polymorphic variants of the cytochrome P450 oxidoreductase and methionine adenosyltransferase 1A genes. Conclusions: Although we studied a small population, we suggest that both clinical and genetic factors might simultaneously be associated with severe myelosuppression developed during TMZ plus RT. However, our results deserve validation in larger prospective studies and, if the factors associated with severe myelotoxicity are validated, dose adjustments of TMZ for those patients may reduce the risk of severe myelotoxicity during the concomitant treatment.